2004
DOI: 10.1007/s11136-004-6189-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Short Form 6D, Standard Gamble, and Health Utilities Index Mark 2 and Mark 3 utility scores: Results from total hip arthroplasty patients

Abstract: Agreement between SG scores and SF-6D and HUI scores was low. The estimate of change in utility associated with THA was lowest for SF-6D. Additional longitudinal studies to compare utility measures appear to be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
64
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 29 publications
10
64
0
Order By: Relevance
“…20 Another study of the HUI 2 and 3 found a large effect size for the change in both measures in osteoarthritis patients before and after total hip arthroplasty. 21 One limitation of our study is that when assessing change, one should compare the change in scores between stable patients and patients who either improve or worsen. In our study, virtually all of the patients improved, making this analysis impossible.…”
Section: Discussionmentioning
confidence: 99%
“…20 Another study of the HUI 2 and 3 found a large effect size for the change in both measures in osteoarthritis patients before and after total hip arthroplasty. 21 One limitation of our study is that when assessing change, one should compare the change in scores between stable patients and patients who either improve or worsen. In our study, virtually all of the patients improved, making this analysis impossible.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many researchers found significant differences in global utility scores obtained by different multi-attribute utility instruments [14][15][16][17][18][19][20][21][22][23][24]. The objective of the present study is to compare the SF-6D and the EQ-5D and to investigate the differences in agreement between them.…”
Section: Introductionmentioning
confidence: 91%
“…A number of studies have now been undertaken to assess the comparative performance of alternative measures (Bosch and Hunink, 2000;Hawthorne et al, 2001;Bosch et al, 2002;Conner-Spady and Suarez-Almzor, 2003;O'Brien et al, 2003;Brazier et al, 2004;Gerard et al, 2004;Hatoum et al, 2004;Holland et al, 2004;Longworth and Bryan, 2003;Marra et al, 2004;Pickard et al, 2005;Stavem et al, 2001;Krahn et al, 2003;Feeny et al, 2004;Szende et al, 2004;Barton et al, 2005;Fisk et al, 2005;McDonough et al, 2005;Marra et al, 2005a,b;Stavem et al, 2005;Lamers et al, 2003;Bharmal and Thomas, 2006). These studies assess measures in terms of criteria such as practicality and validity.…”
Section: Introductionmentioning
confidence: 99%